PENGARUH KEPEMIMPINAN KEPALA PESANTREN DAN MOTIVASI TERHADAP KEDISIPLINAN SERTA IMPLIKASINYA PADA KINERJA USTADZ DI PONDOK PESANTREN DI KOTA SERANG - Usep Usep; Furtasan Ali Yusuf; Basrowi Basrowi (National Conference on Applied Business, Education, & Technology (NCABET), 2021)
This study aims to determine the effect of the leadership of the Islamic boarding school principal and motivation on discipline and its implications for the performance of ustadz in Islamic boarding schools in the city of Serang. The research method used is descriptive, (descriptive method definition). This study prioritizes in-depth analysis of the data and facts found. This type of research is intended to raise facts, circumstances, variables, and phenomena that are happening now and present what they are. The population in this study were all teachers/ustadz or teaching staff in boarding school-based educational institutions in the city of Serang as many as 444 people. The samples used were 215 people. So the author made the decision to use a sampling technique, namely the analytical method used is SEM (Structural Equation Modeling). The results of this study are as follows. Hypothesis testing is carried out based on the results of testing the Inner Model (structural model) which includes r-square output, parameter coefficients and t-statistics. To see whether a hypothesis can be accepted or rejected, among others, by paying attention to the significance value between constructs, t-statistics, and p-values. The hypothesis testing of this research was carried out with the help of the SmartPLS (Partial Least Square) 3.0 software. These values ​​can be seen from the bootstrapping results. The rule of thumb used in this study is t-statistic > 1.96 with a significance level of p-value 0.05 (5%) and a positive beta coefficient. The value of this research hypothesis testing can be shown in the table and the results of this research model can be described as shown in the hypothesis testing carried out on all samples that have been obtained from the questionnaire